The Modelling and Control of a Singular Biological Economic System in a Polluted Environment - Yi Zhang; Yueming Jie; Xinyou Meng (Discrete Dynamics in Nature and Society)
A singular biological economic model with harvesting and stage structure is presented. The local stability of equilibriums of the system is investigated when the economic profit parameter is zero, and the conditions of the singularity induced bifurcation occurring at the positive equilibrium are obtained by the singular systems theory and bifurcation theory. In order to eliminate the singularity induced bifurcation, a state feedback controller is designed by controlling the fishing effort. At last, an application example is given to illustrate the validity of the theoretical results.